-2(3x - 15) = 60
Distribute the -2 on the left side:
-6x + 30 = 60
Subtract 30 from both sides:
-6x = 30
Divide by -6 on both sides:
x = -5
Therefore, the solution to the equation is x = -5.
Solve multi-step linear equations
-2(3x - 15) = 60
3 answers
That's incorrect
Apologies for the mistake. Let's go through the steps again:
-2(3x - 15) = 60
First, distribute the -2:
-6x + 30 = 60
Subtract 30 from both sides:
-6x = 30
Divide by -6 on both sides:
x = -5
Let's double-check our work:
-2(3(-5) - 15) = 60
-2(-15 - 15) = 60
-2(-30) = 60
60 = 60
So the correct solution to the equation is x = -5.
-2(3x - 15) = 60
First, distribute the -2:
-6x + 30 = 60
Subtract 30 from both sides:
-6x = 30
Divide by -6 on both sides:
x = -5
Let's double-check our work:
-2(3(-5) - 15) = 60
-2(-15 - 15) = 60
-2(-30) = 60
60 = 60
So the correct solution to the equation is x = -5.